2014
DOI: 10.1007/s11947-013-1250-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective-Targeted Effect of High-Pressure Processing on Proteins Related to Quality: a Proteomics Evidence in Atlantic Mackerel (Scomber scombrus)

Abstract: The effect of high hydrostatic pressure (HHP) treatment (150, 300 and 450 MPa for 0, 2.5 and 5 min) on total sodium dodecyl sulfate (SDS)-soluble and sarcoplasmic proteins in frozen (-10ºC for 3 months) Atlantic mackerel (Scomber scombrus) was evaluated. Proteomics tools based on image analysis of SDS-PAGE protein gels and protein identification by tandem mass spectrometry (MS/MS) were applied. Total SDSsoluble proteins, composed in high proportion by myofibrillar proteins, were stable under pressurization tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…In general, the higher the pressure, the lower the solubility of the sarcoplasmic proteins, but differences seem to exist among fish species. In mackerel muscle, Manuel Pazos et al (2014) observed that the solubility of sarcoplasmic proteins reduced significantly after pressure processing at 300-450 MPa for 5 min, but not at 150 MPa. In our study, pressure applied during storage was relatively low, but the long time under pressure could be responsible for the low extractability of sarcoplasmic proteins.…”
Section: Protein Stability During Storagementioning
confidence: 99%
“…In general, the higher the pressure, the lower the solubility of the sarcoplasmic proteins, but differences seem to exist among fish species. In mackerel muscle, Manuel Pazos et al (2014) observed that the solubility of sarcoplasmic proteins reduced significantly after pressure processing at 300-450 MPa for 5 min, but not at 150 MPa. In our study, pressure applied during storage was relatively low, but the long time under pressure could be responsible for the low extractability of sarcoplasmic proteins.…”
Section: Protein Stability During Storagementioning
confidence: 99%
“…The MP and the stroma proteins are water insoluble, whereas the SPs are soluble in water. Fish sarcoplasmic proteins (FSP) comprise several types of proteins, including heme proteins [2] (hemoglobin and myoglobin) and enzymes, such as creatine kinase [3], aldolase [3], glyceraldehyde-3-phosphate dehydrogenase (GAPDH) [3], phos-phorylase [4], proteinase inhibitors [5], proteases A and C [6], phospholipase [7], peroxidase [8], transglutaminase (TGase) [9], fructose-bisphosphate aldolase A [10], glycogen phosphorylase [10], beta-enolase [10], triosephosphate isomerase B [10], phosphoglucomutase [10], phosphoglycerate kinase [10], parvalbumins and calmodulins [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the HHP treatments studied 412 in this work induce this targeted degradation only in combination with frozen storage.413Values of total sarcoplasmic protein content in the 2.74-4.22 g/100 g muscle range 414 showed no effect of pressure treatment and frozen storage time. Previous research 415 concerning mackerel showed a decrease on sarcoplasmic protein content when higher 416 pressures (300 and 450 MPa) than in the present case were applied(Pazos et al 2014). 417Over the last decade, proteomics has been successfully applied to evaluate418 quality in food systems including meat, fish, milk and transgenic plants (Gallardo et al419 2013).…”
mentioning
confidence: 43%